The Environmental Impact Analysis of the Scrap Iron Cutting Industry in Kamal-Bangkalan Regency: A Sharia Economic Law Perspective - Wijaya, Dodik Pranata (Fakultas Syariah IAIN madura, 2024)
The sunken or damaged ships cutting scrap metal business in Tanjung Jati Kamal Village, Bangkalan, Madura, has sparked controversy among local residents. Ship dismantling is performed by using heavy machinery which generates dense smoke that affects the ecosystem and poses health risks to the local community. This research aims to assess the severity of the negative consequences of environmental pollution and to investigate the extent to which existing regulations govern the pollution generated. To enhance the study, it examines the principles of sharia economics to determine if these economic activities align with sound economic principles. Utilizing empirical legal research methods, this study relies on primary data obtained directly from the research site through interviews with local residents, workers, and teachers in the vicinity of the industry. Additionally, secondary data is gathered from credible news sources, books, and scientific journals concerning scrap metal cutting activities. The findings indicate that scrap metal cutting contributes to environmental pollution and adversely affects public health, particularly the children. While relevant regulations exist, there is a need for enforcement and more specific law to regulate the standard operating procedures for scrap metal cutters. Moreover, the practice does not align well with the principles of sharia economic law.